An Examination of the Sibling Training Hypothesis for Disruptive Behavior in Early Childhood. Issue 1 (13th February 2017) - Daniel, Ella; Plamondon, André; Jenkins, Jennifer M.
Abstract : Sibling training for disruptive behavior (one sibling teaching another disruptive behavior) is examined during early childhood. We used a conservative, recently developed, statistical model to identify sibling training. Sibling training was operationalized as the cross‐lagged association between earlier child behavior and later sibling behavior, and differentiated from other reasons that contribute to sibling similarity. A three‐wave longitudinal study tracked 916 children ( M age = 3.46, SD = 2.23) in 397 families using multi‐informant data. Evidence for sibling training was found. Earlier younger siblings' disruptive behavior predicted later lower levels of older siblings' disruptive behavior. Thus, the sibling training found in early childhood was producing greater dissimilarity, rather than similarity, on disruptive behavior.